Long-term Research Challenges in Wind Energy - A Research Agenda by the European Academy of Wind Energy - van Kuik, Gijs; Peinke, Joachim (Research Topics in Wind Energy,, 2016)
This book presents the view of European wind energy experts on the long-term research challenges to be solved in order to develop wind energy beyond the applications of today and tomorrow. By this book, the European Academy of Wind Energy (eawe), representing universities and institutes with a significant wind energy programme in 14 countries, wants to: identify current technological and scientific barriers and to stimulate new creative ideas to overcome these barriers define priorities for future scientific research rethink our scientific view of wind energy stimulate the cooperation among researchers in fundamental and applied sciences towards wind energy research The eawe has discussed these long-term research with an explicit focus on a longer-term perspective, in contrast to research agendas addressing short- to medium-term research activities. In other words, this long-term research agenda is driven by problems and curiosity, addressing basic research and fundamental knowledge in 11 research areas, ranging from physics and design to environmental and societal aspects. Because of the very nature of this initiative, this document does not intend to be permanent or complete. It shows the vision of the experts of the European Academy of Wind Energy, but other views may be possible. The eawe sincerely hopes that it will spur an even more intensive discussion worldwide within the wind energy community. .